(untitled) (Third Sector Social Economic Review, 2019)
Developing and accelerating with the industrial revolution, information and communication technologies have lived its golden age in the last fifty years. Recently, especially the invention of computers, internet and smart devices has revolutionized in many areas from the disappearance of national borders, especially communication. These developments in technology have had positive effects in many areas, particularly in industrial production, from agriculture to trade, from education to travel and from entertainment to defense. Although the members of the European Union have mostly been digitalized, Turkey has less progressed in this regard. Developing economic activities in the European Union with parallel to the usage of information is more common than most areas for Turkey. In this study, developments on information-telecommunication sectors in the European Union, Euro Area and Turkey has been discussed. The effects of ICT on the digitalization of the economy have been examined. Despite the positive developments that have occurred in recent years it has not emerged of the economy towards digitalization was achieved in Turkey effectively.